Tamarind (Tamarindus indica L.) Charcoal Color for the Use in Woodcut Printmaking - Narongdecha, Woraunyu; Soodsang, Nirat (Journal of Applied Informatics and Technology, 2025)
This research aimed to study the quality of color produced from tamarind (Tamarindus indica L.) charcoal for use in woodcut printmaking and to compare the color fastness of woodcut prints on various types of paper by examining four color formulas blended with mixtures of Arabic gum and tamarind seed gum. The results revealed that Fabriano paper was the most suitable material for woodcut printmaking using tamarind charcoal color, particularly with Formula 1, which consisted of tamarind charcoal powder, Arabic gum, glycerin (C3H8O3), honey, and deionized water (H2O), as well as Formula 2, which additionally contained indigo (Indigofera tinctoria L.) powder. The comparison of hue and fastness, as determined by a colorimeter, showed that Formula 2 on Fabriano paper exhibited the highest L* value and intensity at 20.80. The +a value indicated a shift toward the green zone, while the –b value indicated a shift toward the blue zone, reaching its highest level at –1.90 due to the addition of indigo powder. Moreover, the average intensity (L* value) on Fabriano paper across the four color formulas showed consistent results. Applying these colors in the woodcut printmaking process demonstrated smooth hues with high intensity, durability, and detailed color expression. In contrast, the color blended with tamarind seed gum showed unstable endurance when applied with a paint roller, resulting in unclear details and hues due to color coagulation. All four color formulas demonstrated good solubility and could be used with either water or deionized water as solvents.